Rezti’s Batik Mboeloe Industry Tegalsari Village Ambulu District Jember from 2011 to 2018 - Desi Putri Rahma Sari; bambang soepeno; sumarjono sumarjono (History Education, University of Jember, 2019)
Batik is a native culture of Indonesia. The first batik making was in Sumber Jambe which is the center of batik in Jember Regency. Problem formulation in this research is how the background of Rezti's Batik Mboeloe industry in Tegalsari Village, Ambulu District, Jember Regency in 2011 and how the development of Rezti's Batik Mboeloe in Tegalsari Village, Ambulu District, Jember Regency, 2011-2018. This research was designed with historical research methods, where the stages of the process consist of 4 steps, namely: 1. Heuristics; 2. Criticism; 3. Interpretation; and 4. Historiography. The development of batik is a form of the creative economy by bringing up various product motif innovations that are able to survive until now. The results of this research, the establishment of the Rezti's Batik Mboeloe industry, have the same potential as Sumber Jambe and Rumah Batik Rolla, although the Ambulu batik industry can be said to be relatively new. Rezti’s Batik Mboeloe Industry offers affordable products with good quality and has batik motifs that are not the same as Sumber Jambe and Rumah Batik Rolla. An interesting development of Rezti's Batik Mboeloe Industry motifs is the lifting of the marine motifs that are characteristic of the Reztik Batik Mboeloe Industry. Suggestions in this study This researcher is expected to be a reference in the development of writing other historical writing studies, this research is expected to provide additional historical knowledge about Indonesian Batik Industry. Keywords: Batik, the development of the Resti Batik Mboeloe Industry